2020
DOI: 10.3389/fimmu.2020.611749
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pro-Fibrotic Macrophage Populations by Single-Cell Transcriptomic Analysis in West Highland White Terriers Affected With Canine Idiopathic Pulmonary Fibrosis

Abstract: Canine idiopathic pulmonary fibrosis (CIPF) affects old dogs from the West Highland white terrier (WHWT) breed and mimics idiopathic pulmonary fibrosis (IPF) in human. The disease results from deposition of fibrotic tissue in the lung parenchyma causing respiratory failure. Recent studies in IPF using single-cell RNA sequencing (scRNA-seq) revealed the presence of profibrotic macrophage populations in the lung, which could be targeted for therapeutic purpose. In dogs, scRNA-seq was recently validated for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 66 publications
5
23
1
Order By: Relevance
“…Previous scRNA-seq studies on BALF from other species ( 14 , 55 ) and on equine peripheral blood ( 53 ) used CD14 to identify monocytes. The expression of this canonical marker was barely detectable in our dataset, similar to previous observations in dog BALF ( 62 ). Yet, equine BALF monocytes have been described as CD14 + cells based on flow cytometric data ( 63 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous scRNA-seq studies on BALF from other species ( 14 , 55 ) and on equine peripheral blood ( 53 ) used CD14 to identify monocytes. The expression of this canonical marker was barely detectable in our dataset, similar to previous observations in dog BALF ( 62 ). Yet, equine BALF monocytes have been described as CD14 + cells based on flow cytometric data ( 63 ).…”
Section: Discussionsupporting
confidence: 91%
“…Cluster Mo/Ma 4 stood out by the co-expression of lymphocyte and monocyte markers. Similar double positive cells were detected in three other BALF scRNA-seq studies ( 4 , 30 , 62 ). This was attributed to either ambient RNA contamination ( 30 , 62 ) or to doublet formation ( 4 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In pathogenic conditions, TRMs can be replaced and joined by recruited monocyte-derived macrophages to orchestrate an immune response ( 10 ). Current studies using single-cell RNA-sequencing (scRNA-seq) have revealed the presence of multiple macrophage subsets with distinct functions in various tissues ( 11 ). For example, Remmerie et al ( 12 ) reported that in fatty liver, hepatic resident KCs were destroyed and replaced by bone marrow-derived macrophages, and those recruited macrophages comprise two subsets resembling either KCs or lipid-associated macrophages expressing Osteopontin.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the circumstances under which pathogens induce long-term changes in TR-AMs or substantial replenishment of different functional Mo-AMs remain to be explored. 106) also used scRNA-seq to characterize macrophage/monocyte cell populations in the BALF from dogs with canine idiopathic pulmonary fibrosis (CIPF) (107) and found that monocytederived macrophages were enriched in profibrotic genes in CIPF. Misharin et al (6) found that during lung fibrosis, AMs are partially depleted and replaced by Mo-AMs.…”
Section: Infections and Lung Injurymentioning
confidence: 99%